Sorption Of Heavy Metals On Biosludge - Aslan, Sukru; Ozturk, Mustafa; Yildiz, Sayiter (European Scientific Journal, ESJ, 2016)
Biosorption of Ni (II) and Cu (II) on the dead cell, which was obtained from the municipal wastewater treatment plant, was studied at various temperatures and pHs. It was found that the heavy metal sorption on the microorganisms was a function of initial solution pH. The lowest qe values were observed at the pH value of 2.0. However, Increasing the pH value of 5.0, sorption capacities increased significantly. The sorption capacity of dead cell was not significantly changed with temperatures. Release of organic materials and ammonium from the cell was also determined in the solution.